A slight trick of the mind a novel - Cullin, Mitch (Talese, 2005)
1947 finds Holmes living in a Sussex farmhouse at 93 with a housekeeper and her son, Roger, who discovers evidence of a case never before reported, a case involving a Mrs. Keller, the long-ago object of Holmes's affection.
Keywords: Holmes, Sherlock (Fictitious character) -- Fiction; Private investigators -- Fiction; Older men -- Fiction; Mystery fiction